The Influence of The Project Based Learning Model on Students' Critical Thinking Skills In The Science Subject of Grade V of UPTD SD Negeri 124401 Pematangsiantar - Manurung, Gaby Margareth; Thesalonika, Emelda; Napitupulu, Rio Parsaoran (Journal of Education and Computer Applications, 2025)
This study aims to determine the effect of the Project Based Learning (PjBL) model on the critical thinking skills of fifth grade students in Natural and Social Sciences (IPAS). The type of research used is quantitative with an experimental method, using a one-group pretest-posttest design. The research subjects were 24 fifth grade students at State Elementary School 124401 Pematangsiantar.The research instrument is a critical thinking essay test that has been validated by experts. The results of the study showed a significant increase in students' critical thinking skills after implementing the PjBL model. The students' average pretest score was 52.5, which increased to 85.33 on the posttest. The N-gain calculation produces a score of 0.70 which is in the high category. This proves that the PjBL model is effective in improving students' critical thinking skills. The implication of this research is that teachers can utilize PjBL as an alternative learning model to improve the quality of students' critical thinking at UPTD SD 124401 Pematangsiantar.